Comprehensive increase in CO2 release by drying–rewetting cycles among Japanese forests and pastureland soils and exploring predictors of increasing magnitude - Y. Suzuki; Y. Suzuki; S. Hiradate; J. Koarashi; M. Atarashi-Andoh; T. Yomogida; Y. Kanda; H. Nagano (SOIL)
It is still difficult to precisely quantify and predict the effects of drying–rewetting cycles (DWCs) on soil carbon dioxide (CO2) release due to the paucity of studies using constant moisture conditions equivalent to the mean water content during DWC incubation. The present study was performed to evaluate overall trends in the effects of DWCs on CO2 release and to explore environmental and soil predictors for variations in the effect size in 10 Japanese forests and pastureland soils variously affected by volcanic ash during their pedogenesis. Over an 84 d incubation period including three DWCs, CO2 release was 1.3- to 3.7-fold greater than under continuous constant moisture conditions (p<0.05) with the same mean water content as in the DWC incubations. Analysis of the relations between this increasing magnitude of CO2 release by DWCs (IFCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="35d0ef4c1024065a846229745b188a25"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-35-2025-ie00001.svg" width="18pt" height="10pt" src="soil-11-35-2025-ie00001.png"/></svg:svg>) and various environmental and soil properties revealed significant positive correlations between IFCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="63e67ec2b1b20349090e8dc0af598eb8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-35-2025-ie00002.svg" width="18pt" height="10pt" src="soil-11-35-2025-ie00002.png"/></svg:svg> and soil organo-metal complex contents (p<0.05), especially pyrophosphate-extractable aluminum (Alp) content (r=0.74). Molar ratios of soil total carbon (C) and pyrophosphate-extractable C (Cp) to Alp contents and soil-carbon-content-specific CO2 release rate under continuous constant moisture conditions (qCO2_soc) were also correlated with IFCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="63135e49ad21d2214c8c451dfba1e14b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-35-2025-ie00003.svg" width="18pt" height="10pt" src="soil-11-35-2025-ie00003.png"/></svg:svg> (p<0.05). The covariations among Alp, total Cp/<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c6f00d13d95b9183e3e2526db4298e27"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-35-2025-ie00004.svg" width="8pt" height="14pt" src="soil-11-35-2025-ie00004.png"/></svg:svg>Alp, and Cp/<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a3a809672b156f3719eee3cbaf593ee5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-35-2025-ie00005.svg" width="8pt" height="14pt" src="soil-11-35-2025-ie00005.png"/></svg:svg>Alp molar ratios and qCO2_soc suggested Alp to be the primary predictor of IFCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="99efa2ded52cb90a031e056655c2d973"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-35-2025-ie00006.svg" width="18pt" height="10pt" src="soil-11-35-2025-ie00006.png"/></svg:svg>. Additionally, soil microbial biomass C and nitrogen (N) levels were significantly lower in DWCs than under continuous constant moisture conditions, whereas there was no significant relation between the microbial biomass decrease and IFCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="7ac8ca304302b1757f1753dcdfec3031"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="soil-11-35-2025-ie00007.svg" width="18pt" height="10pt" src="soil-11-35-2025-ie00007.png"/></svg:svg>. The present study showed a comprehensive increase in soil CO2 release by DWC in Japanese forests and pastureland soils, suggesting that Alp is a predictor of the effect size, likely due to vulnerability of organo-Al complexes to DWC.